The hermit crab–shell relationship through the lens of interaction networks: The use of network metrics and species role across communities. (25th May 2020) - da Silva, Alexandre R.; Rodrigues, Gabriel F.B.; Lima, Daniel; Cobo, Valter J.; da Costa, Rogério C.; Castilho, Antonio L.
Abstract: Hermit crabs are among the most unique crustaceans because they have a non‐calcified pleon, and they often use empty gastropod shells for shelter and protection. The lack of an adequate shell impacts their growth, reproduction and other population features especially because the shell resource might not be found for the entire population or community. This study focuses on the relationship between hermit crabs and their shells using network metrics. We analysed the nestedness, modularity, network specialisation, species specialisation and species role in eight hermit crab communities from two different types of substrate (rock and soft bottom). Most of these communities had a modular and non‐nested pattern. Some communities presented different specialisation levels in terms of resource use (generalist or specialist) with species showing different roles across communities. These patterns could be related to the intra‐/interspecific competition mechanism and by the resource (shell) usage pattern in the different regions. According to species roles, some species characterised as connectors can be addressed as conservation targets. The network approach in hermit crab/shell relationship proved to be an important tool in assessing their interaction in a community level. Abstract :